2010
DOI: 10.1155/2010/365614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano‐Ni Catalyst on the Growth and Characterization of Diamond Films by HFCVD

Abstract: Four different catalysts, nanodiamond seed, nano-Ni, diamond powder, and mixture of nano-Ni/diamond powder, were used to activate Si wafers for diamond film growth by hot-filament CVD (HFCVD). Diamond crystals were shown to grow directly on both large diamond powder and small nanodiamond seed, but a better crystallinity of diamond film was observed on the ultrasonicated nanodiamond seeded Si substrate. On the other hand, nano-Ni nanocatalysts seem to promote the formation of amorphous carbon but suppress trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Diamond with excellent physical and chemical properties such as hardness, great thermal conductivity, chemical inertness and higher carrier mobility is widely used in various fields and many searches carried out on its growth conditions and properties [1][2][3][4][5][6]. Pure diamond is an insulator with wide band gap of 5.5 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Diamond with excellent physical and chemical properties such as hardness, great thermal conductivity, chemical inertness and higher carrier mobility is widely used in various fields and many searches carried out on its growth conditions and properties [1][2][3][4][5][6]. Pure diamond is an insulator with wide band gap of 5.5 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the Csp 2 and Csp 3 peaks are located approximately at 284.3~284.6 eV and 285.0~286.0 eV respectively [37,38].…”
Section: Figurementioning
confidence: 99%
“…Density-functional-based tight-binding MD simulations suggest that the increase in the conductivity is due to the increase of states in the band gap attributed to the bonding disorder and impurities in the grain boundaries 5 . Moreover, vibrational and optical studies on N doped UNCD films have shown a narrowed energy gap with a graphite-like ordered structure, which may be responsible for the high electrical conductivity 6 . Hence, evidence points towards the change in nanostructure of N-doped UNCD relative to undoped UNCD resulting in the increase in conductivity.…”
Section: Ion Beam Irradiation Studies Of Ultrananocrystallinementioning
confidence: 99%